Olfactory disturbances in ageing with and without dementia: towards new diagnostic tools. Issue 7 (20th April 2017) - Gros, A; Manera, V; De March, C A; Guevara, N; König, A; Friedman, L; Robert, P; Golebiowski, J; David, R
Abstract: Background: Olfactory disorders increase with age and often affect elderly people who have pre-dementia or dementia. Despite the frequent occurrence of olfactory changes at the early stages of neurodegenerative disorders such as Alzheimer's disease, olfactory disorders are rarely assessed in daily clinical practice, mainly due to a lack of standardised assessment tools. The aims of this review were to (1) summarise the existing literature on olfactory disorders in ageing populations and patients with neurodegenerative disorders; (2) present the strengths and weaknesses of current olfactory disorder assessment tools; and (3) discuss the benefits of developing specific olfactory tests for neurodegenerative diseases. Methods: A systematic review was performed of literature published between 2000 and 2015 addressing olfactory disorders in elderly people with or without Alzheimer's disease or other related disorders to identify the main tools currently used for olfactory disorder assessment. Results: Olfactory disorder assessment is a promising method for improving both the early and differential diagnosis of Alzheimer's disease. However, the current lack of consensus on which tests should be used does not permit the consistent integration of olfactory disorder assessment into clinical settings. Conclusion: Otolaryngologists are encouraged to use olfactory tests in older adults to help predict the development of neurodegenerative diseases. Olfactory tests should be specifically adapted to assess olfactory disorders in Alzheimer's disease patients.